The Implementation of Yogurt-Making Machine in Dairy Product to Support Self-Reliance of Residents in Batujajar Transit Apartment, Bandung - Muhammad Achirul Nanda; Wahyu Sugandi; Asep Yusuf; Kharistya Amaru (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service proposes the application of a yogurt-making machine for dairy products as a strategy to support residents' self-reliance at the Batujajar Transit Apartment in Bandung. Through modern technology in the milk production process, this community service aims to increase the added value of local dairy products and encourage the active participation of residents in production activities. Community service methods involve surveys, interviews, and direct observations of apartment residents. The number of participants in this training was 20, dominated by housewives, with 62% being aged 20‒25. Based on the analysis, 69.5% of the participants positively assessed this community service activity, including aspects of learning materials, speakers, facilities, satisfaction, and expectations. This implementation also opens up new opportunities for local and regional marketing, increases product competitiveness, and creates an environment that supports economic independence of the farmers. In conclusion, applying a yogurt-making machine for dairy products at the Batujajar Transit Apartment in Bandung is an innovative step toward increasing the economic independence of residents. This community service contributes to developing local products, residents' self-reliance, community empowerment, and regional economic growth.